High Application Rates of Biochar to Mitigate N2O Emissions From a N-Fertilized Tropical Soil Under Warming Conditions - Rittl, Tatiana F.; Oliveira, Dener M. S.; Canisares, Luiza P.; Sagrilo, Edvaldo; Butterbach-Bahl, Klaus; Dannenmann, Michael; Cerri, Carlos E. P. (Frontiers in Environmental Science, 2021)
Biochar application has been suggested as a strategy to decrease nitrous oxide emissions from agricultural soils while increasing soil C stocks, especially in tropical regions. Climate change, specifically increasing temperatures, will affect soil environmental conditions and thereby directly influence soil N2O fluxes. Here, we show that Miscanthus giganteous biochar applied at high rates suppresses the typical warming-induced stimulation of N2O emissions. Specifically, in experiments with high biochar addition (25 Mg ha-1), N2O emissions under 40°C were equal to or even lower compared to those observed at 20°C. In this sense, the mitigation potential of biochar for N2O emissions might increase under the auspices of climate change.